Angle-specific isokinetic shoulder rotational strength can be reliably assessed in collision and contact athletes - Fanning, E.; Falvey, E.; Daniels, K.; Cools, A. (Journal of Sport Rehabilitation, 2022)
An increased understanding of rotational strength as a potential prognostic factor for injury in contact and collision athletes may be important in planning return to sport. The aim of this study was to (1) determine the test-retest reliability of clinically relevant, angle-specific rotational and peak torque measurements in a cohort of uninjured collision and contact athletes; (2) develop a normal descriptive profile of angle-specific rotational torque measurements in the same cohort; and (3) examine the effects of direction and joint angle on shoulder rotational strength interlimb asymmetries. Twenty-three collision and contact athletes were recruited for the interday reliability substudy and 47 athletes were recruited for the remaining substudies. We used intraclass correlation coefficients with 95% confidence intervals to quantify interday reliability of all variables. We used a 2-way repeated-measures analysis of variance to analyze differences in absolute interlimb asymmetries. Interday reliability for the isokinetic strength variables was good to excellent (0.78-0.90) on the dominant side and moderate to good (0.63-0.86) on the nondominant side. Maximum angle-specific torque (as well as peak torque) can be measured reliably in internally and externally rotated positions. A normal profile of clinically relevant, angle-specific shoulder rotational torque measurements for collision and contact athletes has been established which provides a reference when assessing shoulder strength in this population.